The Study of Ten Poems Written by William Blake - Reza, Reza Rezita; Ira Maisarah (UNIB Press, 2024)
This study aims to present findings focused on the analysis of figurative language and central themes in a collection of ten poems by William Blake. Qualitative research methodology is used to conduct a comprehensive analysis. Among the ten poems, the writer discovered that the predominant use of figurative language is metaphors. Furthermore, the theme explored in the poem